A facilitated natural mentoring program: Young adults with autism learn to negotiate college life in a class with university students - Cook, Barbara; Weiss, Deborah; Hodge, Virginia (The ASHA Leader, 2017)
Young adults with autism learn to negotiate college life in a class with university students. © 2017 American Speech-Language-Hearing Association.
Keywords: dept.cmd

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Risk of reading difficulty among students with a history of speech or language impairment: Implications for Student Support Teams - Zipoli, Richard P.; Merritt, Donna D. (Preventing School Failure: Alternative Education for Children and Youth, 2017)
Many students with a history of speech or language impairment have an elevated risk of reading difficulty. Specific subgroups of these students remain at risk of reading problems even after clinical manifestations of a speech or language disorder have diminished. These students may require reading intervention within a general education system of supports and services. The first part of this article describes three speech-language disorders that place elementary students at risk of reading problems: functional speech disorders, childhood apraxia of speech, and specific language impairment. Emphasis is given to research findings on the reading outcomes of students with these disorders. The second part of the article provides recommendations within an RTI framework that will assist Student Support Teams in identifying, monitoring, and supporting these students. © 2017 Taylor & Francis Group, LLC.
Keywords: Assessment; Language impairment; RTI; Reading disability; Speech sound disorders; dept.cmd; peer-reviewed

Unraveling difficult sentences: strategies to support reading comprehension - Zipoli, Jr., Richard P. (Intervention In School And Clinic, 2017)
The ability to understand sentences contributes to students' reading comprehension. However, many reading programs tend to underemphasize explicit instruction aimed at enhancing students' knowledge of sentence structures. Children with language impairments, students with learning disabilities, and English language learners may particularly benefit from instruction that targets potentially challenging sentence structures. This article is designed to help educators and clinicians more effectively identify and teach several sentence structures that can compromise elementary and middle school students' understanding of written text. Four types of sentence structures that may be difficult to process are introduced and systematically explored: (a) sentences with passive verb constructions, (b) adverbial clauses with temporal and causal conjunctions, (c) center-embedded relative clauses, and (d) sentences with three or more clauses. Information is presented on syntactic structures, sources of confusion, developmental considerations, assessment caveats, and instructional strategies.
Keywords: dept.cmd; peer-reviewed; reading comprehension; reading instruction; sentence comprehension; syntax

The effects of auditory training on dichotic listening: A neurological case study - McCullagh, Jennifer; Palmer, Shannon B. (Hearing, Balance and Communication, 2017)
Background: Individuals with neurological impairment have been shown to have deficits in auditory processing abilities. One auditory processing ability shown to be affected is dichotic listening. To date, limited evidence exists demonstrating the effectiveness of dichotic listening intervention on dichotic listening in individuals with neurological impairment. The purpose of this study was to determine the effects of the dichotic listening training on dichotic listening abilities over multiple training periods in an individual with a long-standing and stable neurological history. Method: This study used a case study design. Over the course of 3 years, an individual with dichotic listening deficits following a left cerebral vascular accident underwent multiple auditory training periods using a dichotic listening training paradigm. Initial assessments indicated a bilateral deficit on the Dichotic Digits test with the right ear performing more poorly than the left ear and a right ear deficit on the Dichotic Rhyme test. Training sessions took place 2–3 times per week for a period of 4–11 weeks in the years 2012, 2013 and 2014. Pre- and post-training assessments of dichotic listening and hearing in noise ability were completed for each training period. Results: Results indicated improvements in the trained (right) ear on the Dichotic Digits test following each of the three training periods. Results also indicated stable performance in the right ear on the Dichotic Rhyme test and variable performance on the Words-in-Noise (WIN) test following each training session. Performance on the Dichotic Digits test decreased slightly between training periods; however, overall performance showed improvement over time. Conclusion: These results suggest improved binaural integration abilities as measured by the Dichotic Digits test following dichotic listening training in an individual with neurological impairment. However, the effects of the training did not transfer to tasks of binaural fusion (Dichotic Rhyme test) or hearing in noise (WIN test) tasks. © 2016 International Association of Physicians in Audiology.
Keywords: Article; Auditory training; adult; aphasia; auditory evoked potential; auditory processing disorder; carotid artery obstruction; case report; cerebrovascular accident; dept.cmd; dichotic listening; distortion product otoacoustic emission; follow up; general condition improvement; human; left hemisphere; male; neurological impairment; noise; nuclear magnetic resonance imaging; patient referral; peer-reviewed; priority journal; pure tone audiometry; speech and language rehabilitation; speech audiometry; speech language pathologist; training; tympanometry